THE SPECTRUM OF SENSITIZATION TO AEROALLERGENS AS ONE OF THE RISK FACTORS FOR UNCONTROLLED SEVERE BRONCHIAL ASTHMA - Shakhnoza Abdurasulovna, Ikramova (PT. Antis International Publisher, 2025)
Objective: To evaluate the significance of the spectrum of sensitization to aeroallergens in adult patients with severe bronchial asthma as risk factors for uncontrolled disease progression. Methods: An observational, single-center, cross-sectional study was conducted involving 93 patients diagnosed with severe bronchial asthma. The study examined qualitative and quantitative indicators, including demographic characteristics and comorbid diseases. These factors were analyzed to identify their impact on achieving controlled disease progression. Results: The analysis identified a significant association between aeroallergen sensitization and the difficulty of achieving disease control in patients with severe bronchial asthma. Specific aeroallergens were found to exacerbate symptoms, complicating disease management and increasing the likelihood of uncontrolled progression. Demographic and comorbid factors further amplified these risks, highlighting the multifactorial nature of disease management challenges in this patient population. Novelty: This study underscores the critical role of aeroallergen sensitization in the progression of severe bronchial asthma. By isolating the impact of aeroallergens and integrating demographic and comorbid factors, this research provides a comprehensive perspective on risk assessment and offers potential pathways for improved disease management strategies.